Challenges of Engaging Primary Care Providers in Specialized Telementoring Education About Sickle Cell Disease for Sickle Cell Specialists: Results from the Sickle Cell Disease Training and Mentoring Program for Primary Care Providers (STAMP) Project ECHO - Lisa M. Shook, DHPE, MA, MCHES; Bailey House, MPH; Christina Bennett Farrell, MPH; Rosalyn Stewart, MD; Sophie Lanzkron, MD, MHS; Allison A. King, MD, MPH, PhD; Taniya Varughese, MSOT; J.J. Strouse, MD, PhD; Marsha Treadwell, PhD; Julie Kanter, MD (AJPM Focus)
Introduction: Sickle cell disease (SCD) is an inherited blood disorder affecting approximately 100,000 individuals in the U.S. A lack of knowledgeable providers, particularly for adult patients, has led to a significant number of adults without access to high-quality care. Several federal partners collaborated with the Sickle Cell Disease Treatment Demonstration Program (SCDTDP) grantees to develop and test a national Project ECHO telementoring program targeting primary care providers (PCPs). Methods: Federal partners developed an extensive recruitment and outreach strategy to engage PCPs in the Sickle Cell Disease Training and Mentoring (STAMP) virtual educational (telementoring) program using a multi-pronged recruitment strategy. The SCDTDP grantees created a tailored curriculum of didactic presentations about the management of SCD, especially for PCPs. Results: STAMP hosted 12 sessions over 6 months. Despite the multi-pronged recruitment strategy and tailored curriculum, there were very few PCPs among the 763 attendees. The majority of attendees were hematologists and other community-based advocates with a vested interest in SCD. Conclusions: Despite a federal partnership, the STAMP outreach strategy was unsuccessful in recruiting PCPs to participate in a virtual telementoring education program designed to increase access to care for adults with SCD. STAMP's attendee participation and the lack of engagement by PCPs were unable to significantly show an increase in interest or willingness by PCPs to learn to co-manage SCD care with specialists.